Geodynamic processes in the lower rio Chillon, San Diego - Lima - Guadalupe Gómez, Enrique (2009)
Peru is a mega-diverse country, multicultural, yet there are many and varied phenomena of internal and external geodynamics due to plate tectonics, the climatic diversity and its intricate geomorphology by the presence of the Peruvian Andes and its complex geological history. The province of Lima has a wide internal and external geodynamics, is prone to various geological phenomena, mainly floods, earthquakes, tsunamis and landslides. In several parts of our capital, due to a chaotic urban planning, without technical support, only taking into account the inertia of bureaucratic and corrupt officials have made Lima one of the most vulnerable to the various geodynamic phenomena. Urbanization in San Diego, district of San Martin de Porres, the March 15, 2001, the Chillon River overflowed, breaking a coastal defense. Because of its geomorphology and river geodynamic development has an upper bound to the site of San Diego urba- nization and sits in a hollow, so the river to leave their usual cause, flooded 388 houses, there were 1940 victims and resulted in a sequel economic, social and environmental for a long time. This article attempts to remember and involving people in an effort to create a culture of prevention, which is what often makes them more vulnerable and even claims more victims than the natural geodynamic event itself and in our country the culture of pre- vention is almost null and void, so that it needs to avoid economic losses and social problems resulting from natural disasters.